The Effect of Time Management Discipline on The Academic Stress Level of PAI Students in Completing Assignments - Nagiya; Safitri, Egidia; Saputra, Wahyu (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study examines whether time management discipline affects the level of academic stress among PAI students at IAIN Kerinci. Employing a quantitative method with a descriptive correlational approach, the research involves 55 students selected through simple random sampling. Data were collected using a closed-ended questionnaire comprising a time management scale and an academic stress scale, then analyzed using simple linear regression. The results indicate a significance value greater than 0.05, suggesting no significant influence of time management discipline on academic stress levels. These findings contribute to the literature by demonstrating that time management is not a primary factor in determining students’ stress levels, differing from some previous studies that identified a positive relationship between the two. Practically, the results provide insights for educators and policymakers to consider other factors that may have a more substantial impact on academic stress. This study opens avenues for further research with broader approaches, different methodologies, or additional variables to gain a deeper understanding of this phenomenon.